Physical space and spatiality in Muslim societies: notes on the social production of cities - Rashid, Mahbub (University of Michigan Press, 2021)
"Mahbub Rashid embarks on a fascinating journey through urban space in all of its physical and social aspects, using the theories of Foucault, Bourdieu, Lefebvre, and others to explore how consumer capitalism, colonialism, and power disparity consciously shape cities. Using two Muslim cities as case studies, Algiers (Ottoman/French) and Zanzibar (Ottoman/British), Rashid shows how Western perceptions can only view Muslim cities through the lens of colonization-a lens that distorts both physical and social space. Is it possible, he asks, to find a useable urban past in a timeline broken by colonization? He concludes that political economy may be less relevant in premodern cities, that local variation is central to the understanding of power, that cities engage more actively in social reproduction than in production, that the manipulation of space is the exercise of power, that all urban space is a conscious construct and is therefore not inevitable, and that consumer capitalism is taking over everyday life. Ultimately, we reconstruct a present from a fragmented past through local struggles against the homogenizing power of abstract space"--